The Role of Ecological Values in Fiqh Wudhu’: An Effort to Maintain the Sustainability of Water Resources - Sheila Septiana Dewi; Flourens Ainjellina Bunga P.; Shabrina Shabrina; Erissa Hanifah (International Journal of Religion and Social Community, 2024)
The environmental crisis that includes the scarcity of clean water requires conservation efforts that involve all levels of society, including from a religious perspective. This article discusses the role of ecological values in the fiqh of wudhu’, an important act of worship in Islam that uses water as a means of purification. Using a literature study approach, this article explores how the practice of wudhu’ exemplified by the Prophet Muhammad Saw, teaches water saving and aims to preserve the environment. The results of the study show that ecological values in the fiqh of ablution not only fulfil the ritual requirements of worship but also contribute to the preservation of nature, in line with the concept of maqashid sharia. By instilling ecological awareness in worship practices, Muslims can participate in the preservation of water resources and maintain environmental sustainability as a form of their responsibility as caliphs on earth. The conclusion of this study skors the importance of ecological awareness in daily worship as an effort to form a person who cares about the environment.